Comprehensive understanding of Methyl 2-Naphthyl Ether Molecule by Ab Initio Calculation method - A, Gokila (International Research Journal of Multidisciplinary Technovation, 2023)
The development of the geometrical structure and vibrational wave numbers of Methyl 2-Naphthyl Ether molecule (M2NE) are done with the help of ab initio HF- and Density functional method (DFT/B3LYP) of 6-31G(d, p) basis set. HF and DFT calculations optimize the geometric structure of the selected molecule. The B3LYP density functional method, with a base of 6-31G (d, p), is the best level of theory to repeat the expected wave numbers. Density functional theory was used to calculate the first hyperpolarization (β), electrical dipole moment (μ) of the examined molecule. The results of the calculations also show that a natural bond orbital (NBO) analysis of the M2NE could be performed. The FT-IR and FT-Raman spectrum were theoretically constructed for the title compound. There was a detailed understanding of FTIR and FT-Raman spectrum from experimental analysis. The considered HOMO and LUMO energies demonstrate that charge transfer takes place inside the molecule.